2011
DOI: 10.1111/j.1748-0361.2010.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Free HPV Vaccination Among Young Women: A Comparison of Rural Versus Urban Rates

Abstract: Initial uptake of free HPV vaccination among young rural college women may be problematic. Moreover, uptake of subsequent free doses among rural women may be problematic regardless of whether contact is made in a clinic or through college recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 16 publications
1
48
1
Order By: Relevance
“…Adherence to doses two and three was extremely low, limiting subsequent analysis; results have been presented elsewhere. 6 Table 2 displays the significant bivariate findings. After examining the data for interaction by study site, three variables were found to have interaction at the bivariate level: condom use and hormonal and intrauterine birth control use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adherence to doses two and three was extremely low, limiting subsequent analysis; results have been presented elsewhere. 6 Table 2 displays the significant bivariate findings. After examining the data for interaction by study site, three variables were found to have interaction at the bivariate level: condom use and hormonal and intrauterine birth control use.…”
Section: Discussionmentioning
confidence: 99%
“…36 As posited by the Diffusion of Innovations Theory, knowledge of new innovations, such as the HPV vaccine, is often lower in populations that have limited formal education and lower socioeconomic status (SES) and are less urban. 37 Kentucky as a whole has lower adolescent HPV vaccination rates compared to the United States (40% at least dose one), 4 and Crosby et al 6 found higher vaccination rates among young adult women in urban Kentucky compared to rural Kentucky. Therefore, it is reasonable to extrapolate that our study targeted a population that was clearly undervaccinated compared to national and state data.…”
Section: Study Samplementioning
confidence: 99%
See 1 more Smart Citation
“…33 Other studies have also reported differences by demographic characteristics. 34,[37][38][39][40][41] Using data from the main NIS-Teen phone interview, 35 we focused our analysis on predictor variables that included household (census region, urbanicity, and poverty [compared to 100% of the federal poverty level]), parent (maternal education and preferred language to complete the survey), and adolescent characteristics (race/ethnicity, age at the time of the interview, and private health insurance status).…”
Section: Methodsmentioning
confidence: 99%
“…86 An HPV vaccine uptake study conducted in the US found lower uptake of free vaccines in rural college clinics as compared with urban college clinics. 87 Age-appropriate vaccination rates were also lower among rural children as compared with urban children in Nonsan City in South Korea. 88 Complementary and alternative medicine.…”
mentioning
confidence: 96%